2002
DOI: 10.1074/jbc.m203670200
|View full text |Cite
|
Sign up to set email alerts
|

Rad52 Protein Has a Second Stimulatory Role in DNA Strand Exchange That Complements Replication Protein-A Function

Abstract: Rad52 protein plays a central role in double strand break repair and homologous recombination in Saccharomyces cerevisiae. We have identified a new mechanism by which Rad52 protein stimulates Rad51 protein-promoted DNA strand exchange. This function of Rad52 protein is revealed when subsaturating amounts (relative to the single-stranded DNA concentration) of replication protein-A (RPA) are used. Under these conditions, Rad52 protein is needed for extensive DNA strand exchange. Interestingly, in this new role, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2003
2003
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
1
20
1
Order By: Relevance
“…1E), unlike the observations reported by Sugiyama et al (34). It was reported that Rad51 required 30 -60 mM KCl for heteroduplex joint formation between circular single-stranded DNA and linear double-stranded DNA (43), and that heteroduplex joint formation by Rad52 was stimulated by a lower concentration of KCl, but inhibited by KCl at 50 mM (33). The formation of D-loops by Rad51-Rad52 was decreased 1-3) or RecA (lanes 4 -6) were cleaved by NheI outside the sequence homologous to the pNS11 single-stranded DNA fragments and were incubated at 37°C.…”
Section: D-loop Formation Is Efficiently Promoted In the Presence Of contrasting
confidence: 54%
See 4 more Smart Citations
“…1E), unlike the observations reported by Sugiyama et al (34). It was reported that Rad51 required 30 -60 mM KCl for heteroduplex joint formation between circular single-stranded DNA and linear double-stranded DNA (43), and that heteroduplex joint formation by Rad52 was stimulated by a lower concentration of KCl, but inhibited by KCl at 50 mM (33). The formation of D-loops by Rad51-Rad52 was decreased 1-3) or RecA (lanes 4 -6) were cleaved by NheI outside the sequence homologous to the pNS11 single-stranded DNA fragments and were incubated at 37°C.…”
Section: D-loop Formation Is Efficiently Promoted In the Presence Of contrasting
confidence: 54%
“…In this reaction, Rad52 facilitates the binding of Rad51 to RPA-coated singlestranded DNA and displacement of the RPA (34), and stabilizes the binding of Rad51 to single-stranded DNA (33). In this study, by use of a short single-stranded DNA fragment as a substrate, the requirement of RPA for the reaction was eliminated.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations